Writing the women's movement : a reader - Khullar, Mala (Zubaan, an imprint of Kali for Women, 2005)
This collection provides a synoptic representation of the development of women's studies in India from the late seventies to the present. Divided into different subject areas, the Reader captures the wealth of information in this new field, and looks at how women's studies scholarship has shaped both the academy and spheres of policy-making and advocacy. The essays included here offer not only a curriculum for the teaching of women's studies, but also act as an introductory text for the interested reader. The book represents the work of several women's studies scholars such as Vina Mazumdar, Lotika Sarkar, Devaki Jain, Nirmala Banerjee, Patricia Uberoi, Bina Agarwal, Flavia Agnes, Shohini Ghosh, Malavika Karlekar, Leela Kasturi, Joy Deshmukh, Zoya Hasan, Ratna Sudarshan, Ratna Kapur and others. Themes covered include the women's movement in India, the legal framework, politics, educational intervention, encounters with violence, the family, sexuality and work. Mala Khullar is a freelance consultant and has worked with the Asian Centre for Women's Studies, EWHA Women's University, Seoul; the Aga Khan Foundation, New Delhi; Bernard Van Leer Foundation, the Hague; and the Centre for Women's Development Studies, New Delhi. Contributed articles presented earlier at several seminars on women's studies and feminism in India.